Some results on a class of generalized harmonic numbers - Zhao, Feng-Zhen; Wuyungaowa (Utilitas Mathematica, 2012)
In this paper, we investigate properties of a class of generalized harmonic numbers H n,k,r(α, β). By means of the method of coefficient, we derive a series of identities for H n,k,r,(α, β). We give the asymptotic expansion of H n,k,r,(α,β) when k and r are fixed. Further more we discuss the computation of sums for H n,k,r(α,β) and inverse of binomial coefficient. We give integral representations for sums involving H n,k,r(α,β) and inverse of binomial coefficient.